El problema de la seguridad pública: una aproximación desde la teoría del Estado de Thomas Hobbes - Garcés Arce, Giancarlo W. (2018)
Analyzes the state from the conception Hobbesian and specifies that it has as its main objective to guarantee the security in the political society, displacing other state goals like the common good, the happiness, the protection of the liberties, etc. that They had relevance in the philosophical-political projects of the classical tradition and of not few contemporary philosophers. The Hobbesian state is minimal in relation to a possible intervention in areas such as social and economic, but expansive with regard to measures to combat insecurity. It proposes that this state and the contemporaries of neoliberal orientation are legitimized by their police function in an international scenario marked by fear and insecurity.